Usury Effect on the Economy in Jurisprudence and Iranian Legal System - Khorshidian, A. (Journal of History Culture and Art Research, 2017)
In Islamic economics, the subject of usury, as one of the pillars of the economy is crucial, which can affect, for direct and indirect economic performance of Islamic countries. This study was conducted with the aim of studying and analyzing the problem of usury, in jurisprudence, law, and economics. In this study, we examined the concept of usury, economics, law, and jurisprudence, and then according to importance, based on the destructive effects of usury, the economic health of the community, this issue has been dealt with. In addition, the study is usury, the legal landscape, and patterns of usury-free banking is also described. The research is theoretical and library research was used to collect information, library resources, articles, books, fundamental research, the authoritative publications, conferences and the internet. The findings of this study, suggestions are presented, with a focus on ways out of usury, and also implement banking without usury.